HUBUNGAN MOTIVASI KERJA DENGAN KETERAMPILAN MENGELOLA KELAS GURU PAUD DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU - Siska Lestari; Wilson '; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: This study has to purpose the correlation of work motivation and classroom management skills of early childhood teacher in Simpang Baru Village Tampan Sub-District Pekanbaru. The population in this study were all early childhood teachers in Simpang Baru Village District Tampan Sub-District Pekanbaruas many as 74 teachers consisting of 12 early childhood Institution. The research sample using simple random sampling technique , namely taking a random sample , in it can besamples in this study were as many as 42 teachers who have received training in early childhood institutions in Simpang Baru Village District Tampan Sub-District Pekanbaru.Data collection techniques used are questionnaires and observatio.Data were analyzed using descriptive analysis and correlation analysis product moment that have previously been tested assumptions. The results showed that there was a significant relationship between work motivation and classroom management skills. It is seen from r amounted 0,412.Keywords : Relationship, work motivation, classroom management skill